PENGARUH KERAGAMAN PRODUK, SERVICESCAPE, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN BRASTAGI SUPERMARKET GATOT SUBROTO MEDAN - Edlyn Suwandy Salim; Maisara Batubara; Owen De Pinto Simanjuntak (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
The transformation of consumer behavior from traditional markets toward modern retail has intensified competition in the supermarket industry and pressured management to sustain the factors that drive consumer purchasing decisions. This study aims to analyze the effect of product variety, servicescape, and service quality on consumer purchasing decisions at Brastagi Supermarket Gatot Subroto Medan, which recorded a continuous decline in sales from 2020 to 2024. The research used a quantitative causal approach. The population consisted of all consumers of the supermarket, and a sample of ninety-six respondents was obtained using the Lemeshow formula with accidental sampling. Data were collected through questionnaires measured on a Likert scale and analyzed using multiple linear regression after the classical assumption tests were fulfilled. The findings reveal that product variety, servicescape, and service quality each have a positive and significant effect on purchasing decisions, both partially and simultaneously, with servicescape providing the strongest contribution. The study recommends that management enrich product variety, design a more comfortable and attractive servicescape, and improve service quality to encourage sustainable consumer purchasing decisions